Tissue-specific expression and developmental regulation of the rat apolipoprotein B gene. - Demmer, L A (1986)
Expression of the apolipoprotein B (apoB) gene was examined in a variety of fetal, neonatal, and adult rat tissues by probing RNA blots with a cloned rat apoB cDNA. Among 10 adult male tissues surveyed, small intestine had the highest concentration of apoB mRNA. Its abundance in liver and adrenal gland was 40% and 0.5%, respectively, of that in small bowel, while none was detected in colon, kidney, testes, spleen, lung, heart, or brain. ApoB mRNA is as abundant in 18-day fetal liver as at any subsequent period of hepatic development. In contrast, the concentration of apoB mRNA remains low in fetal intestine until the last (21st) day of gestation, when it increases sharply to levels that are several-fold higher than in the liver. ApoB mRNA levels in fetal membranes harvested during this late gestational period were 10 times greater than in fetal liver. Since the major lipoprotein species in 19-day fetal plasma is low density lipoprotein, these observations suggest that fetal liver, and particularly its functional homologue, the yolk sac, are the principal sites of fetal lipoprotein synthesis at this stage of development. A 20-fold increase in placental apoB mRNA concentrations during the last 48 hr of pregnancy (to a level that is 50% of that encountered in fetal membrane RNA) suggests a specific role for this organ in maternal-fetal lipid transport immediately prior to parturition. Pulse-labeling experiments using 21-day fetal tissue slices showed that the liver synthesizes both apoB-100 (B-PI) and apoB-48 (B-PIII) albeit in somewhat different ratios than the adult organ. Fetal intestine produces almost exclusively the smaller apoB species, while fetal membranes and placenta synthesize only the larger peptide. The postnatal pattern of apoB mRNA accumulation is similar in liver and intestine. Profound decreases were observed during the late suckling and weaning periods, followed by an increase to adult levels. These final concentrations were similar to those encountered at birth. Analysis of these developmental changes offers an opportunity to generate testable hypotheses about the factors that modulate apoB synthesis.